A comprehensive 2 Dimensional and 3 Dimensional FEM study of scarf repair for a variety of common composite laminates under in-plane uniaxial and equibiaxial loadings. (April 2022) - Tashi, Samaneh; Abedian, Ali
Abstract: Due to their potential to recover strength and stiffness with a minimum impact on aerodynamic performance of a damaged structure, scarf repairs are boosted as a viable repair option for primary aero-structures. So far, most of the experimental and numerical studies have been limited to joint specimens and their equivalent 2 Dimensional models and a few number of studies attempted to examine the results using real scarf repair geometry. Suggestions previously made to justify the difference between scarf joint and scarf repair strength and possible solution to diminish the difference are challenged in current work. Here, it is tried to investigate the strengths and shortcomings of 2D scarf joint modelling and their influence on the associated results by promoting 3 Dimensional Finite Element Modelling of complete geometry of the scarf repair. A method to assign material properties to a planar geometry of composite material has been developed that provides the possibility of plane strain, plane stress, and generalized plane strain modelling options of a scarf repair cross section under uniaxial load. Besides, accuracy of scarf joint specimen as a representative to scarf repair to predict load carrying capacity of a circular scarf repair is investigated. The study mainly focuses on 2D and 3D FEM simulation results discrepancies considering the effect of angle ply, cross ply and various stacking sequences of quasi-isotropic laminate under uniaxial and equi-biaxial loads. Results show that the laminate lay-up angles and stacking sequence substantially affect the 2D and 3D simulations agreement. Also, the observed discrepancies in scarf repair and scarf joint results are not limited to the effects of plastic deformation of the adhesive, but it seems the modelling shortcomings greatly affect the results. In overall, the current work demonstrates that for a particular laminate, joint specimen does not represent reasonably a scarf repair. In fact, the load carrying capacity estimated based on joint specimen data can mislead decision making procedure in a way that results in rejection of an eligible repair. To avoid inaccurate strength estimation, a 3D simulation of a scarf repair especially for a load other than uniaxial tension or compression is strongly recommended.